Learning Behavior of Horse Colts: a Case Study of Nepal Cavalry Barrack, Singha Durbar, Kathmandu, Nepal - K.C., Kamal; Singh, N.B. (Journal of Institute of Science and Technology, 2015)
This paper tries to study learning ability behaviors of horse colts in Nepal Cavalry Barrack (NBC), Singha Durbar, Kathmandu. The learning ability of horse colts has been found different behaviors during learning stages. The horses showed different behaviors like fighting, flighting, kicking and biting during trainings. There was no difference of learning ability among three months age of colts. The Learning Ability Index (LAI) has been found as 56, 55, 54, 55, 51 and 64 for the colts A, B, C, D, E and F, respectively. Journal of Institute of Science and Technology, 2015, 20(2): 76-79